Digital Media Consumption and Its Associations with Eating Behaviors, Sleep Quality, and Stress Perception Among University Students in Lahore - Asma Abubakar; Hafiz Syed M. Yasir (Journal of Religion and Society, 2025)
The rapid growth of exposure to the digital media especially in the young adults have highly impacted their life style patterns in terms of sleep and eating habits. Guided by the Bio-Psycho Social Model which explains the biological, psychological and social aspects(Engel 1977). This study investigates the connection of digital media use and its effect on sleep pattern, eating behaviors and perceived stress among Pakistani university students. The data was collected through an online survey which was conducted among 43 university students aged 18-25 from multiple regions of Pakistan, using a snowball sampling technique. The survey assessed digital media use, sleep quality, eating behaviors, and perceived stress. Findings revealed that the students who were highly engaged in social media use reported disrupted sleep patterns alongside irregular eating behaviors. These students also experienced high level of perceived stress compared to those with lower digital media use. The pattern provides the evidence of relation of digital media use with sleeping pattern and eating behaviors and also their relation with high perceived stress, overall giving a cyclic relationship between excessive digital media engagement and its negative effects on psychological wellbeing and lifestyle behaviors. The study highlights the potential impact of digital media on lifestyle patterns and psychological wellbeing, promoting importance of digital hygiene, regular sleeping schedules and, maintaining eating habits which may be helpful to reduce stress among young adults in Pakistan. Keywords: Digital media, perceived stress, sleep patterns, eating habits, mental health, university students https://doi.org/10.5281/zenodo.18433648